Direct influence of human resource management practices on financial performance in Malaysian R&D companies - Adnan, Zurina; Abdullah, Hazman Shah; Ahmad, Jasmine (2011)
Since 1996, the R&D sector in Malaysia has received greater attention than before. Despite fiscal and non-fiscal incentives provided to support the growth of this sector, the level of R&D measured in terms of R&D outputs(i.e. number of patent) is still dismal which is mirrored in the overall performance of local R&D companies. Many studies have investigated factors which influence the performance of organizations. The present study attempts to examine the influence of HRM practices on financial performance of R&D firms. The data for the study were obtained from survey responses from 64 R&D companies. Results of EFA and CFA confirmed the 4 dimensions of HRM practices: participation, reward, training and development, and teamwork practices. Regression results showed participation and reward practices have positive and significant influence on financial performance while training and development practice has negative influence on financial performance. There is no significant relationship between teamwork practice and financial performance. Overall, the findings of the present study provide partial support of universalistic perspective.